Distribution, structural and ecological aspects of the unusual leaf nectaries of Calolisianthus species (Gentianaceae) - Delgado, Marina Neves (2011)
Nectaries in leaves of Gentianaceae have been poorly studied. The present study aims to describe the distribution, anatomy, and ecological aspects of extrafloral nectaries (EFNs) of three Calolisianthusspecies and in particular the ultrastructure of EFNs in Calolisianthus speciosus during leaf development, discussing its unusual structure. Leaves of Calolisianthus species were fixed and processed by the usual methods for studies using light, scanning microscopy and transmission electron microscopy (TEM). Ion chromatography was used to analyze the nectar exudates of C. speciosus. The distribution patterns of nectar secretion units were analysed by ANOVA and t-tests. Two EFNs that can be seen macroscopically were observed at the bases of C. speciosus and C. pendulus leaves. Such large nectaries are absent there in C. amplissimus. Another similarly large EFN is observed at the apex of each leaf in all species. The EFNs at the base of the young leaves in C. speciosus are visited by ants during the rainy season. EFNs are formed by several nectar secretory units (nectarioles) that are present throughout the leaves. Each nectariole is formed by rosette cells with a central channel from which the nectar is released. Channels of old C. speciosus and C. pendulus EFNs were obstructed by fungi. TEM of EFNs in young leaves showed cytoplasms with secretion, small vacuoles, mitochondria, cell wall ingrowth, and plasmodesmata. TEM of EFNs in old leaves demonstrated dictyosomes, plastids, mitochondria, segments of endoplasmatic reticulum, and lipid droplets. The nectar contains sucrose, glucose and fructose.